Optimalisasi Manajemen Kurikulum Merdeka Belajar di PAUD : Langkah-langkah Praktis - Ibdaul Latifah (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2024)
The change in the 2013 curriculum to an independent learning curriculum is a problem for teachers and schools in implementing it. Implementation of the independent curriculum requires good management so that it can run effectively and efficiently. The aim of this research is to describe the management of the independent learning curriculum in improving school quality at Kindergarten ABA 5 Salatiga. This type of research is descriptive qualitative with interviews, observation and documentation as data collection procedures. Data analysis includes data collection, data reduction, data presentation and drawing conclusions. This research uses triangulation of sources and techniques. The results of this research describe the management of the independent curriculum which is divided into 4 aspects, namely planning, organizing, actuating and controlling (POAC). Planning includes needs analysis, looking for reference sources from seminars, workshops and mentoring as well as creating a curriculum design which includes the preparation of learning administration. Organizing includes the division of tasks, principal and functions consisting of the distribution of teaching schedules, schedules for extracurricular and extracurricular assistance, determining methods, media and learning resources as well as learning assessment. Implementation (actuating) includes learning activities, intracurricular, extracurricular and P5 project activities. Assessment (controlling) includes formative and summative assessments which include input, process and learning output.